Tradition,values and socio-economic development - Braibanti , Ralph(ed.); Spengler , Joseph J (ed.) (Durham, 1961)
In this series of nine analytical essays a group of scholars in anthropology, economics, history, political science, and sociology explores the effect of tradition and values in socio-economic development. The editors and five of the contributors were participants in the Duke University Joint Seminar on the Commonwealth in the Spring of 1959. The papers were presented and discussed at the Seminar, except those of Professors Braibanti and Montgomery which were written early in 1960. Professor Montgomery's essay was presented before the graduate seminar of the department of political science at Duke early in 1960 at a session held under auspices of the Commonwealth-Studies Center.
Keywords: Economic development- social aspects .